Pigmented Purpuric Dermatosis Following Tumor Necrosis Factor-Alpha Inhibitor Therapy: A Case Report - Beke, Sinem Kübra; Kaplan, Hüseyin; Cengiz, Gizem; Deniz, Kemal; Kartal, Demet (Archives of Rheumatology, 2025)
Dear Editor, Pigmented purpuric dermatoses (PPD) are chronic skin diseases with recurrent lesions and similar histopathological features, including perivascular lymphocytic inflammation, epidermal changes, and erythrocyte extravasation. Tumor necrosis factor-alpha (TNF-α) inhibitors are widely used in rheumatological disease management and have been associated with several skin reactions; however, reports of PPD are rare. This article presents a case of PPD triggered by TNF-α inhibitor therapy. A 60-year-old female with seropositive rheumatoid arthritis on methotrexate, leflunomide, sulfasalazine, and prednisolone presented to the clinic with worsening symptoms despite combined conventional synthetic diseasemodifying antirheumatic drug (DMARD) therapy. Her history included total thyroidectomy and hypertension. Examination revealed 4 tender and 2 swollen joints, with no other abnormalities. Laboratory tests showed C-reactive protein was 19.64 mg/L, and erythrocyte sedimentation rate was 31 mm/hour. Due to high disease activity (Disease Activity Score 28: 5.97), etanercept was started. In the second month of etanercept treatment, the patient developed rashes on both lower extremities. Physical examination and all laboratory tests, including complete blood count, biochemical tests, autoantibody profiles, complement levels, and viral serologies (hepatitis and HIV), were normal. A dermatology consultation was obtained, and a skin biopsy was performed, revealing findings consistent with PPD. Topical corticosteroids provided partial relief but did not fully resolve the rashes. Given the temporal relationship between etanercept and the development of rashes, the drug was stopped, and adalimumab was started. Therapy was discontinued due to continued joint pain and the persistence of rashes while on adalimumab, and an interleukin-6 inhibitor, tocilizumab, was initiated. At the 1-month follow-up after starting tocilizumab, a notable improvement in rashes was documented. Long-term follow-up is ongoing. Informed consent for publication was obtained from the patient.